2009
DOI: 10.2139/ssrn.1815945
|View full text |Cite
|
Sign up to set email alerts
|

Political Institutions and Street Protests in Latin America

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 26 publications
5
78
0
2
Order By: Relevance
“…Scartascini and Tommasi (2012) argue that citizens choose between institutionalized and non-institutionalized political actions based on their perceived effectiveness. For instance, Machado et al (2011) show that where institutions are strong, actors are likely to participate in the political process through institutionalized arenas. But when institutions are weak, actors are more likely to resort to protests and other unconventional means of participation.…”
Section: Corruption and Education In Democraciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scartascini and Tommasi (2012) argue that citizens choose between institutionalized and non-institutionalized political actions based on their perceived effectiveness. For instance, Machado et al (2011) show that where institutions are strong, actors are likely to participate in the political process through institutionalized arenas. But when institutions are weak, actors are more likely to resort to protests and other unconventional means of participation.…”
Section: Corruption and Education In Democraciesmentioning
confidence: 99%
“…However, they choose a mode of participation that they perceive to be effective (Scartascini and Tommasi 2012). Under weak and corrupt institutions, this means de-emphasizing formal political participation and resorting to more unconventional, non-institutionalized means of participation (Machado et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…26 Hyde and Marinov 2012. 27 Carey 2006;Davis and Ward 1990;Gupta, Singh, and Sprague 1993;Machado, Scartascini, and Tommasi 2011;Moore 1998;Moore 2000. governments tend to respond to domestic threats such as protests with repression and that they are more likely to apply censorship and political restrictions as the frequency and intensity of dissent rises. 28 Sabine Carey, however, found that only guerrilla warfare increases the risk of political repression, whereas non-violent or spontaneous forms of dissent do not create threats substantial enough to warrant a violent government response.…”
Section: Protest and Repressionmentioning
confidence: 99%
“…Similarly, Machado, Scartascini, and Tommasi (2011) examine institutional strength to explain the prevalence of protests. They study seventeen Latin American countries using LAPOP individual survey data finding that "unconventional forms of political participation tend to be chosen more often where institutions are of lower quality" (342).…”
Section: Quality Of Institutionsmentioning
confidence: 99%